Evaluation of a virtual reality-directed brain-gut behavioural treatment inpatient program for patients with inflammatory bowel disease: protocol for a pilot feasibility trial - Melissa DeJonckheere; Peter DR Higgins; Shirley Cohen-Mekelburg; Brian Gutermuth; Ariel Jordan; Gal Hodish; John A Sturgeon; Jeffrey A Berinstein; Jessica Sheehan; Shrinivas Bishu (BMJ Open, 2025)
Introduction Pain is one of the most bothersome symptoms that affects patients with inflammatory bowel disease (IBD) but is often inadequately treated. Inadequate pain control in the inpatient setting not only impacts patients’ experience but increases opioid use and hospital length of stay. Opioids are often considered first-line treatment for severe pain but are associated with significant morbidity and mortality in IBD. Non-steroidal anti-inflammatory drugs are a non-opioid analgesic option, but concerns regarding their contribution to IBD flares have limited their use. Brain-gut behavioural therapies (BGBT), such as cognitive behavioural therapy, meditation and gut-directed hypnotherapy, are effective for pain management and have a role in the treatment of IBD symptoms. However, the use of BGBT in IBD is challenging, given limited access to behavioural health specialists, especially in the inpatient setting. Virtual reality (VR)-directed BGBT programmes can bridge this gap and enhance pain treatment for inpatients with IBD. Therefore, in this study, we aim to establish feasibility and acceptability for a VR-directed BGBT inpatient programme for patients with IBD.Methods and analysis We will recruit 40 patients with IBD who are hospitalised at Michigan Medicine and who endorse IBD-related pain. We will assess patient-reported outcomes (pain rating, IBD-specific symptoms, perceived stress, mood) before and after treatment, cumulative inpatient analgesic requirements and hospital length of stay. Our primary objective will be to establish intervention feasibility defined by the frequency and percentage of enrolled participants that use the VR-directed BGBT inpatient intervention in any capacity. Our secondary objective will be to evaluate intervention acceptability by conducting semistructured interviews with study participants. We will also explore the preliminary effectiveness of VR-directed BGBT on patient-reported outcomes and healthcare utilisation as compared with historic controls.Ethics and dissemination The study was approved by the institutional review board of the University of Michigan Medical School on 10 October 2023 (HUM00240999). All human subjects will be required to sign an informed consent document prior to study participation. Study findings will be reported through peer-reviewed publication.Trial registration number NCT06188793.